BL_GERICHTE 470 2014 270 vom 14. November 2014 , Beschluss des Kantonsgerichts Basel-Landschaft, Abteilung Strafrecht, vom 9. Dezember 2014 (470 14 270) - BL Gerichte (2014)
Untersuchungs- / Sicherheitshaft